HUBUNGAN ANTARA DURASI PENGGUNAAN GADGET DENGAN KUALITAS TIDUR DAN KONSENTRASI BELAJAR PADA SISWA SMA MUHAMMADIYAH PLERET KABUPATEN BANTUL - Tantiana Isnaningsih; Suci Amellia, Zellita (JURNAL SMART ANKes, 2025)
This study aims to determine the corelation between gadget use and sleep quality and learning concentration in students of SMA Muhammadiyah Pleret. Method: This study is a quantitative study using a Cross-sectional approach. Sampling in this study used Total Sampling with a total of 51 students as respondents. Data analysis using Kendall's Tau and Chi Square. Results: The average level of gadget use in SMA Muhammadiyah Pleret students in the moderate category is as many as . And the average level of learning concentration with a low category of respondents, Poor sleep quality of respondents with a percentage of. Based on the results of the chi square analysis, the results were obtained, namely P value 0.013<0.05, there is a corelation between the duration of gadget use and sleep quality in students of SMA Muhammadiyah Pleret, Bantul. Based on the results of the analysis of the Kendal test or the corelation between the duration of gadget use and learning concentration, the results were obtained, namely P value 0.000 <0.05 based on the previously determined value, the significant error value is 5% (0.05), this shows that the P value is smaller than 0.05, it can be interpreted that there is a significant corelation between the two. Keyword: Gadgets, Sleep Quality, Study Concentration.